Proposed ripplon induced weak localization of electrons over liquid helium - Dahm, A. J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
Ripplon induced weak localization is proposed for electrons on a liquid helium surface. Ripplon scattering is quasi-elastic, the ripplons are quasi-static relative to the electron velocity, and the relative change in occupation number of the ripplon state in a scattering event is small. Conditions for the observation of ripplon induced weak localization are calculated.